All quiet on the western front - Remarque, Erich Maria, 1898-1970. (London : Vallantine, 1996)
Depicts the experiences of a group of young German soldiers fighting and suffering during the last days of World War I.
Translation of: Im Westen nichts Neus.
Young Adult.
Keywords: World War, 1914-1918 -- Fiction; World War, 1914-1918 -- Fiction